Perceived stress is associated with impaired artery elasticity: An observational study from the Vara- Skövde cohort - Gábor Szaló; Maria C.M. Eriksson; Margareta Hellgren; Kristin Ottarsdottir; Ying Li; Yun Chen; Karin Rådholm; Lyndia C. Brumback; Matthew Allison; Ulf Lindblad; Bledar Daka (PLoS ONE, 2025)
Background This study aims to determine the association between perceived mental stress and arterial elasticity. Additionally, we will investigate potential effect modifications of sex and antihypertensive medication on this association. Methods Cross-sectional observational study based on the Vara- Skövde Cohort. After excluding individuals with missing information on perceived stress or vascular elasticity, 1015 individuals remained. Perceived stress was evaluated with the Perceived Stress Scale-10 (PSS-10). Small Artery Elasticity Index (SAEI or C2) was estimated from a Windkessel model obtained by applanation tonometry over the arteria radialis. Impaired artery elasticity was defined as the lowest sex-specific quartile of C2. The associations between perceived stress and artery elasticity indices were investigated using linear and logistic regressions with adjustments for possible confounding in different models. Due to significant interactions tests we stratified for men and women and for individuals with and without antihypertensive medication. Results The mean age of study participants was 57 years and women reported significantly higher stress levels on PSS-10 than men [Women: 13.6 ± 5.6; Men: 12.4 ± 5.3; p < 0.01]. Among those 803 individuals who did not take antihypertensive medication, there was a significant association in linear regression between increase in PSS-10 and decrease in C2 (B: −0.2, 95% CI: −0.4- −0.02; p = 0.03) that was lost after adjustment for physical activity (B: −0.16, 95% CI: −0.35–0.03; p = 0.1). In logistic regression analyzes, each increment with 1-SD in PSS-10 was associated with 25% higher odds of having impaired artery elasticity in all models (OR=1.25, 95% CI: 1.01–1.55; p = 0.04). Conclusions Among middle-aged adults without antihypertensive medication, higher perceived stress was associated with impaired arterial elasticity.